Factor VIII companion diagnostic for haemophilia - Hu, Chunxiao; Annese, Valerio F.; Giagkoulovits, Christos; Barrett, Michael P.; Cumming, David R. S. (Frontiers in Bioengineering and Biotechnology, 2022)
Haemophilia is predominantly an inherited disorder that impairs the body's ability to make blood clots, a process needed to stop bleeding. The condition of this disease is complex to manage, but many patients do so through home therapy and often only see their core multidisciplinary healthcare team annually. There is an increasing need for patients to be able to monitor their condition efficiently at home while staying connected with their healthcare team. As a consequence, a low-cost handheld self-monitoring solution for clotting factor is required. Here we have demonstrated a suitable one-step Factor VIII companion diagnostic sensing approach based on a chromogenic assay. The results show comparable performance to the gold standard method. Our approach is able to deliver accurate cost-effective results in under 5 minutes from undiluted human plasma. It has the potential to be able to reduce the human and monetary costs of over- or under-medication for haemophiliacs.